Research Framework: Tourist Walkability and Sustainable Tourism Impact on Residents - Melissa Li Sa Liow (ASEAN Journal on Hospitality and Tourism, 2022)
Tourist walkability has the latent possibility to change how the travelling public moves around tourist destinations. This research paper brings in new perspectives that studies wide-ranging implications of tourist walkability. Set through the lens of Tourism Area Life Cycle, and residents’ perception of community-based tourism, the paper discusses the trepidations and developments in economic, environmental sustainability, quality-of-life satisfaction, and socio-cultural aspects of this urban and recreational tourism activity. A critical review of relevant literature, predominantly from 2011 to 2021 was extracted from ABDC publications, Scorpus, ResearchGate.net and Google Scholar. A new sub-field on tourist walkability and community-based tourism, is of relevance to tourism policymakers and entrepreneurs. A novel research framework is developed. It is proposed for scoping the research context and offer guidelines on proposed themes that can inform scholars when formulating valid and reliable survey measurements for their future works.